2006
DOI: 10.1088/1742-6596/53/1/003
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino mass and New physics

Abstract: We review the present state and future outlook of our understanding of neutrino masses and mixings. We discuss what we think are the most important perspectives on the plausible and natural scenarios for neutrinos and attempt to throw light onto the flavor problem of quarks and leptons. This review focuses on the seesaw mechanism, which fits into a big picture of particle physics such as supersymmetry and grand unification providing a unified approach to the flavor problem of quarks and leptons. We argue that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 178 publications
0
7
0
Order By: Relevance
“…[71] found that with min = 5, S4 experiments could constrain m ν to ±15 meV (68% confidence) when analyzed in conjunction with Planck polarization and DESI data; with min = 50, the error degrades to ±19 meV. Now, neutrino oscillation measurements constrain m ν to have a minimum value of 60 meV [73][74][75][76]. If we take this to be our fiducial value for m ν , going from min = 5 to min = 50 then represents a degradation from a ∼ 4σ to a ∼ 3σ detection.…”
Section: Planckmentioning
confidence: 99%
“…[71] found that with min = 5, S4 experiments could constrain m ν to ±15 meV (68% confidence) when analyzed in conjunction with Planck polarization and DESI data; with min = 50, the error degrades to ±19 meV. Now, neutrino oscillation measurements constrain m ν to have a minimum value of 60 meV [73][74][75][76]. If we take this to be our fiducial value for m ν , going from min = 5 to min = 50 then represents a degradation from a ∼ 4σ to a ∼ 3σ detection.…”
Section: Planckmentioning
confidence: 99%
“…The neutrino sector is still poorly understood and the mechanism that gives rise to their mass is unknown. There are thought to be three active neutrino species, with mass differences measured through solar, atmospheric, reactor, and accelerator neutrino oscillation experiments (for reviews see, e.g., Gonzalez-Garcia and Nir [1], Maltoni et al [2], Smirnov [3], and Feldman et al [4]). The results imply a minimum total mass of 60 meV in a normal hierarchy with two lighter neutrinos and one heavier neutrino, or 100 meV in an inverted hierarchy with two massive neutrinos.…”
Section: Introductionmentioning
confidence: 99%
“…The generic properties of mass textures of quarks and leptons derived in the standard model and in supersymmetric models with a Higgs sector with nontrivial flavours and an S 3 flavour symmetry have been discussed in [45,46]. Recent flavour symmetry models are reviewed in [47,48,49,50], see also the references therein.…”
Section: Introductionmentioning
confidence: 99%